Chromosome organization and gene expansion in the highly fragmented genome of the ciliate Strombidium stylifer. (20th October 2021) - Li, Chao; Chen, Xiao; Zheng, Weibo; Doak, Thomas G.; Fan, Guangyi; Song, Weibo; Yan, Ying
Abstract: Chromosomes are well-organized carriers of genetic information in eukaryotes and are usually quite long, carrying hundreds and thousands of genes. Intriguingly, a clade of single-celled ciliates, Spirotrichea, feature nanochromosomes—also called "gene-sized chromosomes". These chromosomes predominantly carry only one gene, flanked by short telomere sequences. However, the organization and copy number variation of the chromosomes in these highly fragmented genomes remain unexplored in many groups of Spirotrichea, including the marine Strombidium . Using deep genome sequencing, we assembled the macronuclear genome of Strombidium stylifer into more than 18, 000 nanochromosomes (~2.4 Kb long on average). Our results show that S. stylifer occupies an intermediate position during the evolutionary history of Strombidium lineage and experienced significant expansions in several gene families related to guanyl ribonucleotide binding. Based on the nucleotide distribution bias analysis and conserved motifs search in non-genic regions, we found that the subtelomeric regions have a conserved adenine-thymine (AT)-rich sequence motif. We also found that the copy number of nanochromosomes lacks precise regulation. This work sheds light on the unique features of chromosome structure in eukaryotes with highly fragmented genomes and reveals that a rather specialized evolutionary strategy at the genomic level has resulted in great diversity within the ciliated lineages.